A case of acute optic neuritis during pregnancy treated by membrane-based therapeutic plasma exchanges without systemic anticoagulation. (October 2021) - Shkodivskyi, Pavlo; Dressel, Alexander; Handreka, Robert; Schulz, Thomas; Kabtimer, Wondwossen; Stelzle, Fabian; Gudowski, Christin; Pliquett, Rainer U.
Abstract: Introduction: In acute optic neuritis, high dose steroid therapy as first - line treatment is contraindicated in early pregnancy, therapeutic plasma exchanges (TPE) represent an alternative. We report a case of a pregnant woman with progressive, acute optic neuritis subjected to membrane-based therapeutic plasma exchange with extracorporal citrate-based anticoagulation. Case presentation: A 35 year-old second-time pregnant woman (4th week of gravidity) of Caucasian ethnicity complained of visual impairment of the right eye. She was hospitalized for suspected optic neuritis. In the eye exam central and peripheral scotoma of the right side were found. T2 weighted Magnetic-Resonance Imaging revealed an isolated, prechiasmal lesion of the right optic nerve, and the patient had a delayed p100 latency of visually evoked potentials of the right eye. Cerebrospinal-fluid investigation was unrevealing. The diagnosis of right sided optic neuritis was established. Due to early pregnancy, steroids were contraindicated. Visual disturbances further deteriorated by day 2 in hospital. For therapy, 5 sessions of membrane-based therapeutic plasma exchange with albumin solution were performed. An extracorporal anticoagulation using citrate with calcium substitution was applied. After the second session, there was a subjective improvement of symptoms. At discharge on day 14, visual acuity was no longer impaired, sensitivity to bright light remained. In eye exam at 3.5 months after discharge, the patient ha d a complete recovery. Follow-up gynecological exams were unrevealing. Conclusion: This case of unilateral acute optic neuritis supports the view that membrane-based therpautic plasma exchange without systemic anticoagulation represents a safe intervention in pregnancy.